A natureza condominial do fundo de investimento em participações: FIP e a possibilidade de extinção do condomínio por exercício do direito potestativo do cotista - Ribeiro, Leonardo Fernandes da Matta (2016)
This paper assumes that investment funds in participation (FIP) have legal status of a condominium, albeit without denying the importance of the various doctrinal works which attempted to determine other nature based on systematic interpretations or even on analogy. The legal status of condominium is adopted not only as a result of what is provided by the existing law and the regulation imposed by the regulatory agency, but also on the grounds of CVM precedents. Upon the admission of the condominium legal status of the FIP, the paper then proceeds to examine the so-called legal transplant of such investment framework, from its development in certain historical and regional backgrounds, until it reaches the current domestic reality, as well as taking into account its importance and its regulatory framework in relation to proper market development. The paper briefly describes how to establish a FIP, its operation and taxation, the latter being one of the rationales that would justify the choice of this single archetype in relation to what is practiced in certain other jurisdictions. Once taken over the distinguished legal nature of the FIP compared with observed overseas frameworks, the paper reviews the legal consequences arising from its condominium nature especially in light of the five-year limit that the Civil Code provides as its term and also facing the right that condominium member / quotaholder may exercise by requiring the dissolution of the joint ownership. Given the risks that eventual opportunistic behavior by one or more quotaholders may cause it is suggested practical measures in structuring the FIP which may contribute to mitigate the risks exposed throughout the paper.